Neutral Proteases and Cathepsin D in Human Articular Cartilage - Sapolsky, Asher I. (1974)
Proteolytic enzymes have been studied in extracts of human articular cartilage by the use of micromethods. The digestion of hemoglobin at pH 3.2 and of cartilage proteoglycan at pH 5 was shown to be due chiefly to cathepsin D. Cathepsin D was purified 900-fold from human patellar cartilage. Its identity was established by its specific cleavage of the B chain of insulin. At least six multiple forms of cathepsin D are present in cartilage; these corresponded to bovine forms 4-9. Cathepsin D had no action on proteins at pH 7.4. However, cartilage extracts digested proteoglycan, casein, and histone at this pH. The proteolytic activities against these three substrates were purified about 170-, 160-, and 70-fold, respectively. Each activity appeared in multiple forms on DEAE-Sephadex chromatography. The three activities appear to be different since cysteine inhibited casein digestion, aurothiomalate inhibited histone digestion, and neither inhibited proteoglycan digestion. Tests with a wide range of inhibitors and activators suggest that these three activities differ from other neutral proteases described in the literature.